The Implementation of Scaffolding Method in EFL Classroom: An Exploratory Study at Secondary School - Ubaidila, Belly; Safriani, Afida; Salim, Agus (ICONELT, 2024)
This study explores the various kinds and the benefits of scaffolding methods that are implemented in EFL classrooms at the secondary school of MAN Kota Surabaya to enhance language acquisition. Utilizing a qualitative methodology, the research involved systematic classroom observations and student interviews to identify specific scaffolding implemented by the teacher in their teaching process and the benefit that the students get in their learning process. The findings revealed that the scaffolding methods used like visual aids, translation, group work, feedback, and activating prior knowledge significantly contribute to improving students’ linguistic competence, confidence, and engagement. Visual aids improve students’ understanding of abstract concepts. The translation is effective in bridging the gaps in linguistics. Group work can facilitate peer learning and decrease anxiety. Activating prior knowledge can recall and strengthen the previous knowledge, and feedback verbally and physically build up a positive attitude, error correction, and a supportive learning environment. This study explores the various kinds of scaffolding strategies and the benefits for the students in EFL education, showing its benefit to offer tailored instructional support that suits the specific students’ needs